Journalism in Practice: Ethics and Responsibility - Ishani Bhalla; Chanan Ahirwar (Journal of Advanced Research in Journalism & Mass Communication, 2025)
Journalistic Ethics and Responsibilities refer to the set of moral principles and professional standards that guide journalists in their work, ensuring that they report news accurately, fairly, and impartially while maintaining the trust of the public. Ethics in journalism is vital for upholding the integrity of news reporting and ensuring that media serves the public interest, especially in an era where information is abundant and the distinction between fact and opinion is increasingly difficult to discern. In the digital age, the rapid dissemination of information through online platforms has brought about new challenges, such as the spread of misinformation, sensationalism, and biased reporting. Journalists' responsibilities include presenting factual, well-researched, and balanced information, while also considering the impact of their reporting on the public, the individuals involved, and broader societal discourse. Media platforms must also adapt to these challenges, maintaining ethical standards despite technological advancements and the pressure for faster, more engaging content. [1] Renewing the commitment to ethical journalism is essential for preserving the role of media in promoting informed citizenship and supporting democratic processes.